Employers as educators: the role of work placement supervisors in facilitating the transfer of skills and knowledge. Issue 5 (18th August 2021) - Fleming, Jenny; Rowe, Anna D.; Jackson, Denise
ABSTRACT: Work-integrated learning (WIL) placements, undertaken as part of a higher education qualification, are  recognised as a key opportunity for developing talent that is future-capable and can meet contemporary labour market demands. A workplace supervisor that can facilitate this learning is critical to the experience. The purpose of this study was to explore workplace supervisors' views on their contributions as educators, and their role as facilitators for the transfer of skills and knowledge from university to the workplace. Semi-structured interviews were undertaken with 24 WIL host supervisors of students from Business, Sociology and Sports and Recreation in three universities across Australia and New Zealand. The findings confirm WIL supervisors do consider themselves as educators, moving beyond training students on how to complete tasks, to helping them develop the graduate capabilities needed for contemporary work. Further, they consider some skills to be transferable, rather than context-specific and particular to certain industries or workplace cultures. Yet, views on who should be responsible for transfer were mixed with disparities between the higher education curriculum and workplace tasks considered problematic. Key strategies and behaviours for facilitating transfer are identified to help workplace supervisors and educators create appropriate WIL experiences that integrate university and workplace learning.